Stakeholder-driven development of a cloud-based, satellite remote sensing tool to monitor suspended sediment concentrations in major Bangladesh rivers. (November 2020) - Beveridge, Claire; Hossain, Faisal; Biswas, Robin Kumar; Haque, AM Aminul; Ahmad, Shahryar Khalique; Biswas, Nishan Kumar; Hossain, Md Amirul; Bhuyan, Md Arifuzzaman
Abstract: Environmental decision-support tools often fail to be effectively applied in society because tools are "use-inspired" rather than "user-ready." Stakeholder engagement by researchers is frequently the missing, critical component. Here, university researchers collaborated with the Bangladesh Water Development Board (BWDB) in developing a cloud-based, satellite remote sensing tool for monitoring suspended sediment concentrations (SSC) in major Bangladesh rivers. Bangladesh faces complex river erosion and sediment management challenges. The tool helps to overcome BWDB's constraints of limited resources and ground-based monitoring capacity. The tool maps estimated SSC over satellite images and provides long-term estimated SSC time series at user-designated points. The key elements of success in the engagement process were the partnership and trust between the researchers and stakeholder; stakeholder leadership and ownership; diversity of stakeholder roles engaged; researcher's understanding of the stakeholder, problem, and context; and open-source, easy-to-use tool. Weaknesses in the engagement process can be improved on in future work. Highlights: Describes stakeholder engagement process between early-career researcher and Bangladesh water governance agency. Co-developed a cloud-based, satellite remote sensing tool for monitoring river suspended sediment concentrations. Demonstrate generalizable engagement approach, evaluate key strengths and weaknesses, and present lessons learned. Successful process due to long-term partnership, stakeholder ownership, and researcher's understanding of broader context.